Werden Anorexia nervosa-Patienten seelisch wieder gesund?: Ergebnisse einer 12-Jahreskatamnese von 103 Patienten - Deter, Hans-Christian; Herzog, Wolfgang; Manz, Rolf (Zeitschrift für psychosomatische Medizin und Psychoanalyse, 1994)
In a long-term follow-up study over 12,7% (range 9—19) years, 16 of 103 patients with anorexia nervosa died. 92% of the survivors were followed up personally, 7% only indirectly. The paper presents the psychological changes assessed by means of the Anorexia Nervosa Symptom Score in the course of the disorder. At the time of catamnesis, the psychic condition of the patients was furthermore evaluated in more detail by procedures of independent assessment (DSM III-R, Impairment-Score (IS), Confidant Rating) as well as by using different instruments of self-assessment (Eating Attitude Test, Eating Disorder Inventory, Social Netword Questionnaire). In a case conference taking into account all relevant findings, 40,1% of the patients were found to be healthy, 30,4% were considered to still show severe psychic disorders, and 29,4% were rated as desolate. These results suggest that part of the patients become psychicalls healthy again. Altogether, however, the long-term prognosis of anorexia has to be regarded as rather poor. In einer Langzeitverlaufsuntersuchung über 12,7 (9—19) Jahre waren von 103 Anorexia nervosa-Patenten 16 verstorben. 92% der Überlebenden konnten persönlich und 6% indirekt nachuntersucht werden. Die Arbeit stellt die psychologischen Veränderungen im Krankheitsverlauf anhand des Anorexia nervosa-Symptomscores dar. Die seelischen Befunde zum Katamnesezeitpunkt werden darüber hinaus mit Methoden der Fremdbeurteilung (DSM III-R, Beeinträchtigungsschwerescore (BSS), Confidantrating), wie auch durch Selbstbeschreibungsinstrumente (Eating Attitude- Test, Eating Disorder Inventory, Sozialer Netzfragebogen) differenziert. Aufgrund einer Fallkonferenz wurden unter Einbeziehung aller relevanten Befunden 40,1% der Patienten als gesund, 30,4% als weiterhin deutlich psychisch gestört und 29,4% als desolat (chronische Anorexie, verstorben) eingestuft. Diese Ergebnisse weisen darauf hin, daß ein Teil der Patienten seelisch wieder gesund wird. Die Prognose der Anorexia nervosa im Langzeitverlauf ist aber als insgesamt ernst anzusehen.